The mutational landscape of early‐ and typical‐onset oral tongue squamous cell carcinoma. Issue 4 (4th November 2020) - Campbell, Benjamin R.; Chen, Zhishan; Faden, Daniel L.; Agrawal, Nishant; Li, Ryan J.; Hanna, Glenn J.; Iyer, N. Gopalakrishna; Boot, Arnoud; Rozen, Steven G.; Vettore, Andre L.; Panda, Binay; Krishnan, Neeraja M.; et al.
Abstract : Background: The incidence of oral tongue squamous cell carcinoma (OTSCC) is increasing among younger birth cohorts. The etiology of early‐onset OTSCC (diagnosed before the age of 50 years) and cancer driver genes remain largely unknown. Methods: The Sequencing Consortium of Oral Tongue Cancer was established through the pooling of somatic mutation data of oral tongue cancer specimens (n = 227 [107 early‐onset cases]) from 7 studies and The Cancer Genome Atlas. Somatic mutations at microsatellite loci and Catalog of Somatic Mutations in Cancer mutation signatures were identified. Cancer driver genes were identified with the MutSigCV and WITER algorithms. Mutation comparisons between early‐ and typical‐onset OTSCC were evaluated via linear regression with adjustments for patient‐related factors. Results: Two novel driver genes ( ATXN1 and CDC42EP1 ) and 5 previously reported driver genes ( TP53, CDKN2A, CASP8, NOTCH1, and FAT1 ) were identified. Six recurrent mutations were identified, with 4 occurring in TP53 . Early‐onset OTSCC had significantly fewer nonsilent mutations even after adjustments for tobacco use. No associations of microsatellite locus mutations and mutation signatures with the age of OTSCC onset were observed. Conclusions: This international, multicenter consortium is the largest study to characterize the somatic mutational landscape of OTSCC and the first to suggest differences by age of onset. This study validates multiple previously identified OTSCC driver genes and proposes 2 novel cancer driver genes. In analyses by age, early‐onset OTSCC had a significantly smaller somatic mutational burden that was not explained by differences in tobacco use. Lay Summary: This study identifies 7 specific areas in the human genetic code that could be responsible for promoting the development of tongue cancer. Tongue cancer in young patients (under the age of 50 years) has fewer overall changes to the genetic code in comparison with tongue cancer in older patients, but the authors do not think that this is due to differences in smoking rates between the 2 groups. The cause of increasing cases of tongue cancer in young patients remains unclear. Abstract : This study identifies 7 putative oral tongue squamous cell carcinoma driver genes ( TP53, CDKN2A, CASP8, NOTCH1, FAT1, ATXN1, and CDC42EP1 ) and shows that early‐onset oral tongue squamous cell carcinoma has a significantly smaller somatic mutational burden that is not explained by differences in tobacco use.